Discussion - Of Mr. Firmstone's Paper on An Unusual Blast-Furnace Product; and Nickel in Some Virginia Iron-Ores (see p. 547) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
John J. Porter, Cincinnati, Ohio (communication to the Secretary *):—The remarks of Mr. Firmstone concerning the presence of nickel in Oriskany ores, call to my mind some additional evidence on this point. In 1903, while engaged in the determination of zinc in a number of samples of ore from the Oriskany mine of the Alleghany Ore & Iron Co., I was surprised to discover the presence of nickel and cobalt. As far as I was then able to discover, their present;! had up to this time remained unnoticed. The amounts ranged from 0.05 up to 0.10 per cent. of the combined oxides, and while no attempt was made to separate the metals, the presence of both nickel and cobalt was conclusively proven. Since that time I have learned that traces of these metals are of quite general occurrence in Virginia iron-ores, and more especially in the ores of the Potsdam formation from the western slopes of the Blue Ridge. In certain manganese-ores from this formation, I have found as high as 0.50 per cent. of nickel and cobalt oxides. Any one interested in this subject will find further information in a volume l written by Andrew 8. McCreath, and printed in 1884 for distribution by the Norfolk & Western railway. A number of complete and accurate analyses of Virginia iron-and manganese-ores are given, and practically all show nickel and cobalt in appreciable quantity. Still another source of information on the occurrence of nickel in iron-ores in the United States, for which I am indebted to Charles Catlett, is found in the Tenth Census. Several analyses of Oriskany ores are given: all of which show the presence of nickel, with less cobalt, while the single representative from the Potsdam formation shows nickel, with no cobalt.